Ante bellum houses of the Bluegrass : the development of residential architecture in Fayette County, Kentucky - Lancaster, Clay (University of Kentucky Press, 1961)
The ante bellum homes of Lexington and Fayette County, Kentucky, are both more numerous and more distinctive in design than those of many communities of similar age. Founded in 1775, Lexington by the turn of the century had become the chief cultural center north of New Orleans and west of the Alleghenies. During the eight decades between the Revolution and the Civil War, Fayette County was the focus of converging streams of immigration, and a phenomenal amount of building activity took place in Lexington and the surrounding area. Although local builders followed the trends of national architec.